Analisis Penggunaan Sistem Informasi Pemerintah Daerah dalam Penyusunan Laporan Keuangan Pemerintah Daerah di Kabupaten Solok - Sofida, Yeni; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the analysis of the use of regional government information systems in preparing regional government financial reports in Solok Regency. Type of quantitative descriptive research. The population in this study was all Financial Management Employees in the Solok Regency Government totaling 120 people and the sample in this research was 120 Financial Management Employees in the Solok Regency Government. This research analyzes data using the Partial Least Square (PLS) approach. Data analysis techniques are the R-Square value, the direct influence hypothesis (Direct Effects) and the indirect influence hypothesis (Indirect Effect). The results show a positive and significant influence of information quality on trust. There is a positive and significant influence of system quality on trust. There is a positive and significant influence of information quality on user satisfaction. There is a positive and significant influence of system quality on user satisfaction. There is a positive and significant influence of trust on user satisfaction. Trust does not mediate the effect of information quality on user satisfaction. Trust mediates the effect of system quality on user satisfaction